Are statins associated with decreased tooth loss in chronic periodontitis? - Barry G. Saver (Blackwell Synergy, 2007)
Aim: To evaluate whether statin use was associated with decreased tooth loss among patients with chronic periodontitis. Material and Methods: We evaluated administrative health plan data from 1996 to 2002 covering dental and periodontal treatment utilization, dental extractions, and prescription medication fills of 12,631 adults aged 48–64 in 2002. With tooth loss as the outcome, we evaluated a number of different patterns of statin prescription across time in multivariate generalized linear models. Results: Unadjusted, statin use was associated with increased tooth loss. After adjustment for potential confounders, there was no suggestion of either increased or decreased tooth loss associated with statin use. Conclusions: Statin use was not associated with either a decreased or an increased risk of tooth loss.